2022
DOI: 10.3389/fimmu.2021.753754
|View full text |Cite
|
Sign up to set email alerts
|

Overload of the Temporomandibular Joints Accumulates γδ T Cells in a Mouse Model of Rheumatoid Arthritis: A Morphological and Histological Evaluation

Abstract: Recently, it has been reported that γδ T cells are associated with the pathology of rheumatoid arthritis (RA). However, there are many uncertainties about their relationship. In this study, we investigated the morphological and histological properties of peripheral as well as temporomandibular joints (TMJ) in a mouse model of rheumatoid arthritis with and without exposure to mechanical strain on the TMJ. Collagen antibody-induced arthritis (CAIA) was induced by administering collagen type II antibody and lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Secondly, the intermediary roles played by specific immune cell markers in this association were observed. While B cells play a pivotal role in RA pathogenesis by producing autoantibodies, studies in collagen antibody-induced arthritis mice revealed no significant changes in B cell numbers within the TMJ compared to control mice ( 11 ). However, a notable increase in T cells was observed in TMJ when mechanical stress was applied to the mandibular condyle, suggesting their potential involvement in RA-associated TMDs ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the intermediary roles played by specific immune cell markers in this association were observed. While B cells play a pivotal role in RA pathogenesis by producing autoantibodies, studies in collagen antibody-induced arthritis mice revealed no significant changes in B cell numbers within the TMJ compared to control mice ( 11 ). However, a notable increase in T cells was observed in TMJ when mechanical stress was applied to the mandibular condyle, suggesting their potential involvement in RA-associated TMDs ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…While B cells play a pivotal role in RA pathogenesis by producing autoantibodies, studies in collagen antibody-induced arthritis mice revealed no significant changes in B cell numbers within the TMJ compared to control mice ( 11 ). However, a notable increase in T cells was observed in TMJ when mechanical stress was applied to the mandibular condyle, suggesting their potential involvement in RA-associated TMDs ( 11 ). Our results suggest that the impact of RA on TMDs may be mediated through reduced CD3 expression on CD4 T cells in serum and an elevated percentage of CD25++ CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation